ChemInform Abstract: Understanding the Formation of Salt‐Inclusion Phases: An Enhanced Flux Growth Method for the Targeted Synthesis of Salt‐Inclusion Cesium Halide Uranyl Silicates. Issue 40 (September 2016) - Morrison, Gregory; Smith, Mark D.; zur Loye, Hans‐Conrad
Abstract: Single crystals of [Cs3 F][(UO2 )(Si4 O10 )] (I), [Cs2 Cs5 F] [(UO2 )2 (Si6 O17 )] (II), [Cs9 Cs6 Cl] [(UO2 )7 (Si6 O17 )2 (Si4 O12 )] (III), and [Cs2 Cs5 F] [(UO2 )3 (Si2 O7 )2 ] (IV) are grown using an enhanced flux growth involving mixtures of UF4 or UO2 and SiO2 covered with a of 9:11 molar mixture of CsF and CsCl (Ag tubes, 800 °C, 12 h).